A load-complementarity combined flexible clustering approach for large-scale urban energy-water nexus optimization. (15th July 2020) - Wang, Wei; Jing, Rui; Zhao, Yingru; Zhang, Chuan; Wang, Xiaonan
Graphical abstract: Highlights: A flexible clustering approach is proposed for large-scale energy-water nexus. Electricity-cooling-heating-water-hydrogen integrated model is built. The flexibility of typical density-based spatial decomposition is improved. Demand complementarity effect is considered during clustering. The combined index assessment is integrated into the clustering and optimization. Abstract: Modeling and optimization of a large-scale urban energy-water nexus system with sufficient spatial resolutions is a complex challenge. By proper clustering technique, a large-scale problem could possibly be divided into small ones with high spatial resolution and accuracy. Existing literature tends to lower the complexity of large-scale urban energy system problem by accumulating demand profiles on the spatial dimension. This study proposes a flexible clustering approach based on density clustering method with combined index assessment process. The flexible approach considers not only the spatial dimensions but also the complementarity effect of different demand profile and control the computational time of system design and optimization. The approach can increase the clustering flexibility by providing more clustering options than conventional method, take advantages of complementarity effect to further improve the system economic performance and control the solving time in an acceptable range. The proposed approach is evaluated by a case study of a new business district in Shanghai, China with a proposed future energy-water nexus system. After three combined index assessment, 45 new clustering maps are generated by the flexible clustering approach and the final optimal solution obtained by the proposed approach can further obtain 6.74% cost savings compared with conventional clustering approach.